Prestasi adaptif perkhidmatan awam : kajian literatur mengenai intervensi pengurusan dalam pembangunan kepimpinan dan rangka kerja - Muhamad Syahrom Ismail,; Fatimah Wati Halim, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Civil servants need to adapt to the ever-changing conditions especially in the face of the COVID-19 pandemic. Based on current uncertain challenges, the existing approach of public service management in addressing change management may not be optimally implemented. Having considered the need to manage continuous change and ensure that civil servants are always prepared to face unexpected challenges, the development of the adaptive performance of civil servants is seen as a better approach. Recognizing the need, the authors carried out conceptual parallel studies on management interventions in leadership development based on literature studies identified in the current study of Park and Park (2019) on adaptive performance and its antecedents. Although several studies examined by Park and Park (2019) showed that many interventions can improve adaptive performance, public service management should consider a few things before they are implemented based on the context of changes and challenges during the COVID-19 pandemic. Based on the main findings obtained from the study of the literature, the framework involving management intervention in leadership development has been prepared for the consideration of the management of the next government department/agency. Overall, this study can help improve operational effectiveness in the public service, thus helping other reviewers explore other interventions to improve adaptive performance in the public service.